Chronotope as a Narrative Technique in Virginia Woolf’s Mrs. Dalloway - Boukhalfa, Boutheina; Adi Touhami ,Ibtissem (FACULTY OF LETTERS AND FOREIGN LANGUAGES DEPARTMENT OF ENGLISH, 2017)
Time and place are thought to be two important concepts in the analysis of literary works. These concepts form the background and they have a direct influence on the other components of the literary work such as plot, themes, etc. Michael Bakhtin (1981) thought that these two components have got equal significance and found out the term “chronotope”, which includes the combination of time and place. The aim of this study is to analyse and use the concept of chronotope as a narrative technique in Virginia Woolf’s Mrs Dalloway, which is considered to be one of the most important works of British modern literature. Because of the inevitable range of change, the perception of time and space completely changed in modern times. Chronotopic reading of Mrs Dalloway became fundamental to understand the spatial and temporal connections in the novel